ANALISIS KESALAHAN PESERTA DIDIK KELAS VIII SMP PEMBANGUNAN LABORATORIUM UNP DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA BERDASARKAN ANALISIS KESALAHAN NEWMAN - Aulia Rahma (Jurnal Edukasi dan Penelitian Matematika, 2022)
This study aims to describe the errors made by students in solving math story problems based on Newman's error analysis. In this study, using 5 questions about the story of the material of rank and root form given to 26 students of class IXC SMP Pembangunan Laboratorium UNP. The questions were analyzed using Newman's error analysis and interviews were conducted with 6 selected students to analyze and find out the causes of student errors. Analysis of the data used is the analysis of Miles and Huberman and the validity of the data is tested by data triangulation. The results showed that the most frequent Newman error indicator was the process error indicator with a percentage of 76.9% and the least error was an error in understanding the question with a percentage of 49.2%. Factors that cause student errors are the low talent of students, students' habits of not repeating learning and inaccuracies. Keywords – Newman Error Analysis, Story Problem, eksponen and rooth form